Comparasion Of Insult Regulation Towards President/Vice President In The Decree of The Constitutional Court - Robinsius Asido Putra Nainggolan (Constitutionale, 2021)
The reform of criminal law in Indonesia, which has become one of the discourses, is the Article regarding insults to the President and Vice President in the 2019 RUUKUHP. The government re-included several articles of insulting the president in the Draft Criminal Code formulation, which the Constitutional Court deleted through Decision Number: 013.022/PUU IV/2006. So the problem in this research is how the policy formulation of offense against the President and Vice President is following the formulation of the RUUKUHP and how the comparison of articles on insulting the President and Vice President in the formulation of the Draft Criminal Code with the Constitutional Court Judge Decision No: 013.022/PUU IV/2006. The research method used is juridical normative based on secondary data through library research data collection and data analysis. The discussion results show that the policy for the formulation of offense against the President/Vice President following the formulation of the RUUKUHP is an effort to provide legal protection to the President/Vice President as a symbol in state life. Comparing articles regarding insults to the President and Vice President in the formulation of the RUUKUHP with the Constitutional Court Decision No: 013.022/PUUIV/2006 have both similarities and differences.